Germicidal Activity against Carbapenem/Colistin-resistant Enterobacteriaceae Using a Quantitative Carrier Test Method. (4th October 2017) - Kanamori, Hajime; Rutala, William A; Gergen, Maria; Sickbert-Bennett, Emily; Weber, David J
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE), conferring broad resistance to most β-lactam antibiotics, are involved in healthcare-associated outbreaks via medical equipment and environmental surfaces. Colistin-resistant Enterobacteriaceae carrying the mcr-1 are currently a global health concern since colistin is often a last-line antibiotics used to treat multidrug-resistant organisms, including CRE. However, susceptibility to germicides (e.g., disinfectants, antiseptics) for these pathogens is poorly understood. We assessed efficacy of various germicides against carbapenem/colistin-resistant Enterobacteriaceae . Methods: We tested 21 different germicides with 2 dilutions of sodium hypochlorite against 3 species of Klebsiella pneumoniae carbapenemase (KPC)- producing Enterobacteriaceae and Escherichia coli carrying mcr-1 . The disc-based quantitative carrier test method was used to assess the bactericidal activity of chemical germicides since it is believed to produce results similar to those actually encountered in healthcare settings compared with suspension testing. An inoculum containing approximately 10 6 test organisms with 5% fetal calf serum (FCS) was placed on each disk. The dried inoculum was exposed to the test germicide for 1 minute exposure time at room temperature then neutralized. Compared with mean carrier control counts, the log10 reduction of the test organism for each germicide was calculated. Results: Figure 1 shows efficacy of germicides with active ingredient, product name, and classification against test organisms. Overall, most germicides reached at least 3-log10 reduction (20/22 [91%] for KPC K. pneumoniae, 0/22 for E. cloacae, 18/22 [82%] for KPC E.coli, 19/22 [86%] for MCR-1 E. coli ). Furthermore, all germicides, except for two products (1% chlorhexidine gluconate plus 61% ethyl alcohol, 3% hydrogen peroxide) against MCR-1 E. coli, demonstrated at least 2-log10 reduction for these pathogens even in challenging test conditions (5% FCS and 1 minute exposure time). Conclusion: Our study suggests that germicides commonly used in healthcare facilities may be effective against carbapenem/colistin-resistant Enterobacteriaceae when used appropriately. Disclosures: D. J. Weber, PDI: Consultant, Consulting fee.